Creation of a successful multidisciplinary course in pediatric neuro‐oncology with a systematic approach to curriculum development. Issue 7 (1st December 2020) - Moreira, Daniel C.; Gajjar, Amar; Patay, Zoltan; Boop, Frederick A.; Chiang, Jason; Merchant, Thomas E.; Santiago, Teresa; Schaeffer, Elizabeth; Sonnenfelt, Jason; Andujar, Allyson; Shuler, Ana; Caniza, Miguela A.; et al.
Abstract : Background: The St Jude Global Academy Neuro‐Oncology Training Seminar (NOTS) is a hybrid course in pediatric neuro‐oncology specifically designed for physicians from low‐income and middle‐income countries. Methods: The curriculum for the course was created by conducting a targeted needs assessment that evaluated 11 domains of care for children with central nervous system (CNS) tumors. The targeted needs assessment was completed by 24 institutions across the world, and the data were used to define 5 core elements included in the 2 components of the NOTS: a 9‐week online course and a 7‐day in‐person workshop. Participant acquisition of knowledge and changes in clinical behavior were evaluated as measures of success. Results: Teams from 8 institutions located in 8 countries enrolled in the online course, and it was successfully completed by 36 participants representing 6 specialties. On the basis of their performance in the online course, 20 participants from 7 institutions took part in the on‐site workshop. The participants exhibited improved knowledge in core elements of treating children with CNS tumors, including barriers of care, possible solutions, and steps for project implementation ( P < .0001). All participants expressed a belief that they acquired new concepts and knowledge, leading to changes in their clinical practice. Those present at the workshop created an international multidisciplinary group focused on treating CNS tumors in low‐income and middle‐income countries. Conclusions: By using a hybrid online and in‐person approach, the authors successfully created a multidisciplinary course focused on pediatric CNS tumors for resource‐limited settings. Their experience supports this strategy as a feasible mechanism for driving further global collaborations. Abstract : The St Jude Global Academy Neuro‐Oncology Training Seminar is a hybrid course in pediatric neuro‐oncology specifically designed for physicians from low‐income and middle‐income countries. The course successfully improves the knowledge and behavior of participants in key concepts related to treating children with central nervous system tumors in resource‐limited settings, supporting the strategy as a feasible mechanism for driving further global collaborations.